(untitled) (Journal on Excellence in College Teaching, 2024)
Faculty and students often are not on the same page regarding what college-level learning means or requires. Students who expect to receive “the truth” or “the answer” from their professors are unnerved when they hear phrases like “it depends.” Instructors who expect students to be able to apply course concepts to new learning situations are disheartened when they struggle. If a goal of higher education is to engage students in intellectual growth, then we must begin by addressing this learning expectations disconnect.